PENYELESAIAN SISTEM DESKRIPTOR LINIER DISKRIT BEBAS WAKTU DENGAN MENGGUNAKAN METODE DEKOMPOSISI KANONIK - Uswatun Hasanah (Jurnal Matematika UNAND, 2012)
The linear discrete descriptor systems are used in many applications, espe-cially in mathematical modeling for biology, economics and electrical engineering. In thispaper, the solving of invariant time linear discrete descriptor systems using the canonicaldecomposition method was studied. The canonical decomposition method reduces thesystems under consideration into two simple subsystems. The solution is obtained fromtwo simple subsystems. An example is given to illustrate this method.